Kajian Hak Harta Perempuan dengan Pendekatan Ideologis - Hayati, Ulfi (PSGA LP2M IAIN Pontianak, 2023)
This paper looks at the origin of women's property rights using an ideological approach, namely the Qur'anic interpretation of women's property rights. The origin can be seen before and as difficult as Islam. Before Islam, women showed disdain and had them disastrous in life. When a mother gives birth to a daughter, the child is buried alive to cover up the family's disgrace. It is also not uncommon for women to become objects or prey for satisfaction, and inheritance that can be inherited and married by their own children. Regrettably, women cannot own anything that belongs to them, women are only slaves who serve their employers. This is the life of women before the religion of Islam was brought by Muhammad. On the contrary, after Islam was widespread throughout the country, women's degrees began to be recognized and valued in people's lives. Among those who nurture and educate girls with a good education, the guarantee for him is heaven. Women are like queens in a kingdom, they also have the right to what has been given to him. Thus, the existence of women before and after Islam is very different in life.